2009
DOI: 10.1128/jb.00148-09
|View full text |Cite
|
Sign up to set email alerts
|

OpnS, an Outer Membrane Porin ofXenorhabdus nematophila, Confers a Competitive Advantage for Growth in the Insect Host

Abstract: The gammaproteobacterium Xenorhabdus nematophila engages in a mutualistic association with an entomopathogenic nematode and also functions as a pathogen toward different insect hosts. We studied the role of the growth-phase-regulated outer membrane protein OpnS in host interactions. OpnS was shown to be a 16-stranded ␤-barrel porin. opnS was expressed during growth in insect hemolymph and expression was elevated as the cell density increased. When wild-type and opnS deletion strains were coinjected into insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…This porin lack was associated with a decrease in the virulence index of K. pneumoniae strains, as reflected by the significant modification of the kinetics of the killing of the nematodes even in strains that overexpressed an efflux pump. Involvement of porins in bacterial virulence has been mentioned by some teams (12,29,31,35). However, this is the first time that a correlation between porin expression and level of virulence has been demonstrated for K. pneumoniae.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This porin lack was associated with a decrease in the virulence index of K. pneumoniae strains, as reflected by the significant modification of the kinetics of the killing of the nematodes even in strains that overexpressed an efflux pump. Involvement of porins in bacterial virulence has been mentioned by some teams (12,29,31,35). However, this is the first time that a correlation between porin expression and level of virulence has been demonstrated for K. pneumoniae.…”
Section: Discussionmentioning
confidence: 90%
“…However, this is the first time that a correlation between porin expression and level of virulence has been demonstrated for K. pneumoniae. Porins expressed by the bacteria under conditions present in the host body contribute to the stability of the outer membrane (35) and also participate in the bacterial defense against the chemical immune system, e.g., defensins and antimicrobial peptides (29). Moreover, they also play a role in bacterial adhesion and invasion (12,31).…”
Section: Discussionmentioning
confidence: 99%
“…Porins are furthermore not only known to be involved in recognition by the host (e.g. in the squid symbiont Vibrio fischeri , Nyholm et al, 2009 ), but were also shown to be involved in survival in and communication with the host in other intracellular and pathogenic bacteria, rendering Vibrio cholerae and Xenorhabdus nematophila more resistant against antimicrobial compounds ( Mathur and Waldor, 2004 ; van der Hoeven and Forst, 2009 ). As Riftia trophosome tissue has antimicrobial effects ( Klose et al, 2016 ), and considering that Riftia might employ histone-derived antimicrobial peptides to modulate the symbiont’s cell division ( Hinzke et al, 2019 ), Endoriftia porin may enable the symbionts to reject antimicrobial compounds produced by the host.…”
Section: Discussionmentioning
confidence: 99%
“…Since xenocoumacin is the major antibiotic produced by X. nematophila these findings suggested that the NRPS encoded by xcnA may be involved in xenocoumacin synthesis. OmpR is a global response regulator involved in the regulation of outer membrane porin genes, various transporters, virulence genes, flagella and curli fibres (Mattison et al ., 2002; Feng et al ., 2003; Goh et al ., 2004; Jubelin et al ., 2005; Park and Forst, 2006; van der Hoeven and Forst, 2009).…”
Section: Introductionmentioning
confidence: 99%